(untitled) (Research, Society and Development, 2021)
The present work had as general objective to analyze the legislation and strategies that guided the State of Piauí in guarantee the Right to Food to the students of the State Public System during the Pandemic crisis by Covid-19. It is a documentary analysis of the main normative acts that deal with the right to food in the school environment. To delimit the analysis period, we identified the legislation, the decrees, and the strategies against the pandemic in the context of school feeding published that implemented from March to December 2020. In this perspective, the evolution of human rights is presented, from the human right to food to its conception as a guarantee in the Brazilian constitutional text and the importance of the National School Feeding Program (PNAE) in consolidating the Right to Food. It is noteworthy that the PNAE is the oldest and most important food program in Brazil’s public food and nutrition security policy. Finally, an analysis of the legislation and strategies of the State of Piauí was carried out to guarantee public school students access to adequate food during the period of suspension of classes due to the Covid-19 crisis.